The Virago story : assessing the impact of a feminist publishing phenomenon - Riley, Catherine E. (Protest, culture and society, 2018)
"The 1970s witnessed a renaissance in women's print culture, as feminist presses and bookshops sprang up in the wake of the second-wave women's movement. At four decades' remove from that heady era, however, the landscape looks dramatically different, with only one press from the period still active in contemporary publishing: Virago. This engaging history explains how, from modest beginnings, Virago managed to weather epochal transformations in gender politics, literary culture, and the book publishing business. Drawing on original interviews with many of the press's principal figures, it gives a compelling account of Virago's place in recent women's history while also reflecting on the fraught relationship between activism and commerce"--